Restorative Justice in Medical Case Resolution for Health and Medical Workers - Munandar, M. Aris; Muchtar, Syamsuddin; Ramli, Rafika Nurul Hamdani (Journal of Law, Politic and Humanities, 2025)
This research discusses the application of restorative justice in the settlement of criminal cases in the health sector, especially those involving medical personnel and health workers. The background of this research is the increasing number of cases of alleged medical malpractice that have created a negative stigma against the medical profession. The purpose of this study is to analyze the restorative justice arrangements in Law Number 17 of 2023 concerning Health, as well as assess the urgency of more detailed technical arrangements. This research uses a normative legal research method with a statutory approach. The results show that although Article 306 of the Health Law has opened up space for case settlement through restorative justice, there are no clear indicators regarding the types of criminal offenses that can be resolved with this mechanism. In addition, Government Regulation No. 28 of 2024 has not yet regulated the technical implementation, and there is no clarity on the division of authority between professional organizations and law enforcement officials. The findings of this study emphasize the importance of drafting independent technical regulations so that restorative justice in medical cases can be implemented effectively, fairly, and provide legal protection for all parties involved.